Population abundance of oil palm pollinating weevil, Elaeidobius kamerunicus faust and its relation to fruit set formation in mineral and peat soil areas in Peninsular Malaysia - Saharul Abillah Mohamad,; Siti Nurulhidayah Ahmad,; Muhammad Nurul Yaqin Syarif,; Mohamad Rosman Sulaiman,; King, Jie Hung; Muhamad Azmi Mohammed,; Mohamed Mazmira Mohd Masri, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
The oil palm pollinating weevil, Elaeidobius kamerunicus, plays a vital role in the oil palm fruit formation process. An insufficient pollinator population may cause poor fruit set formation, resulting in a high number of parthenocarpic fruitlets and malformed fruit bunches. This study examines the population level of E. kamerunicus at two sites in Peninsular Malaysia and its relation to the fruit set formation. Each site represented different soil types, viz, mineral and peat soil. Preliminary results of the study showed that both sites had high adult weevil population density, averaging at 68662.87/hectare and 89270.93/hectare for peat soil and mineral soil, respectively. The average sex ratio of inflorescences in peat soil area (58.09%) was significantly higher than those at mineral soil area (45.01%, F = 6.75, P = 0.016). The average fruit set percentage in both study areas was satisfactory (more than 60%). The average fruit set in mineral soil area (83.08%) was significantly better than those recorded at the peat soil area (69.47%, F = 4.42, P < 0.05). Even though there are differences in terms of the population level of the pollinator, the fruit set formation in both areas is still satisfactory.